Dynamic security and routing strategy-based health care monitoring with IoT in wireless sensor network - Dr. M. Vijayakumar, Dr. Archana Ganesh Said, V.S.Triveni, Professor, Dr.J.Srimathi , Naresh Kumar Sripada, Dr.A.Anandh, Dr.K.P.Malarkodi (South Eastern European Journal of Public Health, 2025)
Wireless sensor networks are frequently utilized because they enable the provision of at least a range of access services. It is currently being used in the healthcare industry to monitor the patients. To do analysis and make decisions, the data gained through monitoring has been gathered in various cloud environment servers and places. This scenario faces various challenges in recent Internet of Things devices in data security and route security. Such threats affect security performance and decision-making. Although several data encryption and routing techniques have been explored in the literature, they often fall short of achieving the desired level of security. An effective service-centric data security and routing solution is proposed to address this problem. The method focused on monitoring the mentally disabled on the working of their anatomy and updating the data to the cloud data server. The technique utilizing both IoT devices and the infrastructure of a wireless sensor network, which includes sensor nodes. This technique keeps track of various physiological parameters, including heart rate, temperature, and blood pressure. The features monitored have been transmitted to the cloud data server which is updated in the database. The data transmission is performed by choosing an optimal route by measuring route-specific data security measure value for different routes, which is measured based on the number of IoT devices, Hop count, transmission history of the route, and each IoT device. Similarly, the data security is enforced by adapting Feature Orient Adaptive Encryption scheme which considers the source which generates the data and request.